New joints: Private providers and rising demand in the English national health service - Elaine Kelly; George Stoye (Institute for Fiscal Studies (IFS), 2016)
Reforms to public services have extended consumer choice by allowing for the entry of private providers. The aim is to generate competitive pressure to improve quality when consumers choose between providers. However, for many services new entrants could also affect whether a consumer demands the service at all. We explore this issue by considering how demand for elective surgery responds following the entry of private providers into the market for publicly funded health care in England. For elective hip replacements, we find that demand shifts account for at least 7% of public procedures conducted by private hospitals. These results are robust to instrumenting for location using the presence of existing healthcare facilities. Exploiting rarely used clinical audit data, we show that these additional procedures are not substitutions from privately funded procedures, and represent new surgeries, at least within a given year. The increase in volumes resulting from a demand shift improve consumer welfare, but impose fiscal costs, and do not contribute the original aim of the reforms to stimulate competition.
Keywords: I11; I18; L33; 330; public service choice; healthcare demand; geographic variation